Perlindungan Konsumen Terhadap Peredaran Kosmetik Yang Tidak Mencantumkan BPOM : (Studi di BPOM Mataram) - Restia Noviani Putri; Sahruddin Sahruddin (Fakultas Hukum Universitas Mataram, 2022)
This research aimed to reveal the legal arrangements of cosmetic products that are distributed without valid permission from the authority and to find out efforts undertaken by BPOM in supervising these products. The investigation is carried out by applying the normative-empirical legal research method. It is evident that BPOM has supervised these cosmetics by conducting inspections of distribution, taking cosmetics samples and laboratory testing to ensure their safety and quality. Moreover, the consumer is also protected through several preventive policies including direct in-field visitation to vendors and the public on the importance of understanding cosmetical products standard and socializing potential sanctions of selling illegal and hazardous cosmetics. In terms of repressive legal enforcement, the criminal law system and subsystem are involved, including relevant institutions such as police, judiciary, court and correctional institutions to tackle the distribution of illegal cosmetics.